Oxidative Stress and Inflammation Response Following Aerobic Exercise: Role of Ethnicity - McKenzie, M. J.; Goldfarb, A.; Garten, R. S.; Vervaecke, L. (International Journal of Sports Medicine, 2014)
African-Americans are at a significantly greater risk for developing several diseases and conditions. These conditions often have underlying oxidative stress mechanisms. Therefore the purpose of this investigation was to ascertain the post-exercise oxidative response to a single bout of aerobic exercise in African-American and Caucasian college-age females. A total of 10 African-American and 10 Caucasian females completed the study. Each subject had her VO2 max measured while exercising on a treadmill. A week later, each subject returned to the laboratory and performed a 30-min run at 70% of her VO2max. Blood samples were taken immediately prior to and following exercise for analysis. Lipid hydroperoxides, protein carbonyls, malondialdehyde, xanthine oxidase, glutathione in the reduced (GSH) and oxidized (GSSG) forms, TNFα and interleukin 6 were measured from blood taken before and after exercise. Significance was set at p≤0.05 a priori. Xanthine oxidase was the only measure that did not significantly increase following exercise. All other markers showed a significant elevation in response to the exercise bout with no difference between groups except that the Caucasian group had significantly higher malondialdehyde post-exercise compared to the African-American group. This cohort of college-age African-American and Caucasian females showed little difference in their response to a single 30-min run at 70% of their max in the markers of oxidative stress within the blood.
Keywords: glutathione; lipid hydroperoxides; malondialdehyde; protein carbonyl; xanthine oxidase; interleukin 6